Towards a Consensus-based Classification of Childhood Arterial Ischemic Stroke - Bernard, Timothy J. (2011)
BACKGROUND AND PURPOSE: The implementation of uniform nomenclature and classification in adult arterial ischemic stroke (AIS) has been critical for defining outcomes and recurrence risks according to etiology and in developing risk-stratified treatments. In contrast, current classification and nomenclature in childhood AIS are often overlapping or contradictory. Our purpose was to develop a comprehensive consensus-based classification system for childhood AIS. METHODS: Utilizing a modified-Delphi method, members of the International Pediatric Stroke Study (IPSS) developed the Childhood AIS Standardized Classification and Diagnostic Evaluation (CASCADE) criteria. Two groups of pediatric stroke specialists from the IPSS classified seven test cases using two methods each: 1) classification typical of the individual clinician’s current clinical practice, 2) classification based on the CASCADE criteria. Group 1 underwent in-person training in the utilization of the CASCADE criteria. Group 2 classified the same cases via an online survey including definitions but without training. Inter-rater reliability (IRR) was assessed via multi-rater unweighted kappa statistic. RESULTS: In Group 1 (with training), IRR was improved using CASCADE criteria (κ=0.78, 95% CI=[0.49, 0.94]) compared to typical clinical practice (κ=0.40, 95%CI=[0.11, 0.60]). In Group 2 (without training), IRR was lower than among trained raters, (κ=0.61, 95%CI=[0.29,0.77]); but higher than current practice (κ=0.23, 95%CI=[0.03,0.36]). CONCLUSIONS: A new, consensus-based classification system for childhood AIS, the CASCADE criteria, can be used to classify cases with good IRR. These preliminary findings suggest that the CASCADE criteria may be particularity useful in the setting of prospective multicenter studies in childhood-onset AIS, where standardized training of investigators is feasible.